2019
DOI: 10.1111/codi.14543
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of recovery and outcome after left and right colectomy

Abstract: Aim The present study aimed to compare functional recovery and surgical outcomes after left and right colectomies. Method Consecutive elective left and right colon resections for benign and malignant indications, performed between 2011 and 2016 and recorded in a prospectively maintained enhanced recovery database, were analysed. Demographic and surgical items, as well as functional recovery and 30‐day complications, were compared between left‐sided and right‐sided colectomies. Multivariable analysis was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…Right colectomy for cancer is a standardized procedure carried out by most general surgeons [10]. Because of the preponderance of terminal ileal disease and a 10-year risk of surgical resection of almost 50%, many patients with CD eventually require ileocolonic resections [11, 12]. Because of the complexity of medical management requiring thorough surveillance and follow-up, patients with CD are treated in dedicated inflammatory bowel disease units [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Right colectomy for cancer is a standardized procedure carried out by most general surgeons [10]. Because of the preponderance of terminal ileal disease and a 10-year risk of surgical resection of almost 50%, many patients with CD eventually require ileocolonic resections [11, 12]. Because of the complexity of medical management requiring thorough surveillance and follow-up, patients with CD are treated in dedicated inflammatory bowel disease units [13].…”
Section: Discussionmentioning
confidence: 99%
“…The older cancer cohort, presenting with more age-related comorbidities, was prone to both medical complications and increased 30-day mortality. Functional recovery (mobilization and alimentation) was likely accelerated in the younger CD population, which may have further contributed to decreased medical complications [12]. While LOS was similar in both groups (70% discharged within 5 days), (risk-adjusted) readmissions were higher in patients with CD.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the underlying pathology does not influence surgical outcomes, similar as the present study, which focused in particular on functional outcomes. However, recent studies revealed delayed GI function associated with colectomy for inflammatory bowel disease [24, 25]. Dai et al [24] suggested preoperative conditioning (normalization of albumin levels, steroid weaning) and early management of postoperative sepsis as efficient measures to reduce POI.…”
Section: Discussionmentioning
confidence: 99%
“…Although the CRCs are mainly distinguished with embryonic origin, there are great significances existing between the LCCs and RCCs in various clinical aspects, such as metastasis tendency, survival and prognosis, chemotherapy drugs, immunotherapy, and sensitivity of molecularly targeted drugs, etc. (5)(6)(7). The difference in prognosis makes colon cancer sidedness a criterion for predicting prognosis of all clinical stages (8).…”
Section: Introductionmentioning
confidence: 99%